Abnormal collagen deposition mediated by cartilage oligomeric matrix protein in the pathogenesis of oral submucous fibrosis - Yafei Xiong; Xuechun Li; Bincan Sun; Jie Zhang; Xiaoshan Wu; Feng Guo (International Journal of Oral Science)
Abstract Abnormal accumulation of collagen fibrils is a hallmark feature of oral submucous fibrosis (OSF). However, the precise characteristics and underlying mechanisms remain unclear, impeding the advancement of potential therapeutic approaches. Here, we observed that collagen I, the main component of the extracellular matrix, first accumulated in the lamina propria and subsequently in the submucosa of OSF specimens as the disease progressed. Using RNA-seq and Immunofluorescence in OSF specimens, we screened the cartilage oligomeric matrix protein (COMP) responsible for the abnormal collagen accumulation. Genetic COMP deficiency reduced arecoline-stimulated collagen I deposition significantly in vivo. In comparison, both COMP and collagen I were upregulated under arecoline stimulation in wild-type mice. Human oral buccal mucosal fibroblasts (hBMFs) also exhibited increased secretion of COMP and collagen I after stimulation in vitro. COMP knockdown in hBMFs downregulates arecoline-stimulated collagen I secretion. We further demonstrated that hBMFs present heterogeneous responses to arecoline stimulation, of which COMP-positive fibroblasts secrete more collagen I. Since COMP is a molecular bridge with Fibril-associated collagens with Interrupted Triple helices (FACIT) in the collagen network, we further screened and identified collagen XIV, a FACIT member, co-localizing with both COMP and collagen I. Collagen XIV expression increased under arecoline stimulation in wild-type mice, whereas it was hardly expressed in the Comp -/- mice, even with under stimulation. In summary, we found that COMP may mediates abnormal collagen I deposition by functions with collagen XIV during the progression of OSF, suggesting its potential to be targeted in treating OSF.